Two-Year Syndromal and Functional Recovery in 219 Cases of First-Episode Major Affective Disorder With Psychotic Features - Tohen, Mauricio; Hennen, John; Zarate, Carlos M.; Baldessarini, Ross J.; Strakowski, Stephen M.; Stoll, Andrew L.; Faedda, Gianni L.; Suppes, Trisha; Gebre-Medhin, Priscilla; Cohen, Bruce M. (The American journal of psychiatry, 2000)
OBJECTIVE: Psychotic affective disorders are the most prevalent idiopathic psychoses, but their outcome from onset has rarely been studied. In this study, the authors determined the rate and latency of syndromal recovery and rates of functional recovery after first lifetime hospitalization in patients with first-episode psychotic affective disorders. METHOD: From first lifetime hospitalization in 1989-1996, 219 patients with a DSM-IV psychotic affective illness were assessed at intervals over 24 months. Time to syndromal recovery (no longer meeting DSM-IV episode criteria) was assessed by survival analysis, and functional recovery (regaining baseline vocational and residential status) was rated. Factors associated with recovery were identified by bivariate and multivariate methods. RESULTS: By 3, 6, 12, and 24 months after first hospitalization, syndromal recovery was attained by 65.1%, 83.7%, 91.1%, and 97.5%, respectively, of subjects. Time to syndromal recovery (6.1 weeks to 50% of subjects recovered) was shorter for patients who had bipolar disorder, were married, were age 30 or older at onset, lacked comorbidity, required relatively brief hospitalization, and received fewer medicines. Functional recovery by 6 (30.4%) and 24 months (37.6% of patients) was 2.6-2.7 times less likely than syndromal recovery; 63.1% of those recovering syndromally did not recover functionally by 2 years. Functional recovery was associated with older age at onset and shorter hospitalization. Annual recovery rates remained stable as mean hospital length of stay decreased 3.6-fold over the 8-year study period. CONCLUSIONS: Syndromal recovery was attained by most psychotic affective disorder patients soon after hospitalization, but only one-third recovered functionally by 24 months. The findings suggest that these very common psychotic illnesses can carry a grave functional prognosis from the initial episode and first hospitalization.